Quality of life in long-term breast cancer survivors – a 10-year longitudinal population-based study. (August 2013) - Koch, Lena; Jansen, Lina; Herrmann, Antje; Stegmaier, Christa; Holleczek, Bernd; Singer, Susanne; Brenner, Hermann; Arndt, Volker
Abstract: Background. Breast cancer survivors may experience adverse effects of cancer and/or treatment years after completion of therapy, which can considerably decrease quality of life (QoL). Little is known about the time course of QoL in breast cancer survivors beyond the fifth year post-diagnosis, when routine follow-up care has usually terminated. We therefore explored in detail whether and to what extent restrictions in breast cancer survivors persist and whether changes or aggravations in QoL occurred over time. Material and methods. QoL was assessed 1, 3, 5, and 10 years post-diagnosis in a population-based cohort of initially 387 female breast cancer patients from Saarland (Germany), using the EORTC QLQ-C30 and QLQ-BR23. Time course of QoL over 10 years post-diagnosis was assessed for survivors and survivors' QoL was compared cross-sectionally to the German general population after adjustment for age. Results. A total of 182 out of 238 patients alive (76.5%) responded in the 10-year, 160 patients (67.2%) participated in all follow-ups. Although breast cancer survivors and controls reported comparable general health and overall QoL, survivors reported significantly more restrictions on most functioning and symptom scales at each follow-up. Detriments in various QoL dimensions (e.g. physical and social functioning; pain, financial difficulties) aggravated from year 5 to 10. Generally, restrictions were largest for the youngest survivors. Conclusion. Relevant restrictions in QoL persist over years in breast cancer survivors and affect predominantly younger women. The aggravation of restrictions in QoL beyond the fifth year may indicate deficits in health care and psychosocial support of breast cancer patients after completion of routine follow-up care.